Oral health in an urban slum, Nigeria: residents' perceptions, practices and care-seeking experiences - Mary E. Osuh; Gbemisola A. Oke; Richard J. Lilford; Jackson I. Osuh; Folake B. Lawal; Shakeerah O. Gbadebo; Eme Owoaje; Akinyinka Omigbodun; Babatunde Adedokun; Yen-Fu Chen; Bronwyn Harris (BMC, 2023)
Abstract Background/introduction One of the key recommendations for the new WHO global strategy for oral health is inclusion of disadvantaged populations and their engagement in policy dialogues such that their needs and views are addressed in policy decisions. Objectives This study explored oral health perceptions, practices and care-seeking experiences of slum residents in Ibadan, Nigeria. Method Focus group discussions (FGD) were conducted with family health-decision makers in an urban slum site. Oral health perceptions, practices, and care-seeking experiences were discussed. FGDs were recorded, transcribed, and translated. ATLAS.ti qualitative research software was deployed for analysis using thematic analysis. Results Six FGD sessions, divided by gender and age, were conducted between September-October 2019, (N = total 58 participants, aged 25 to 59 years). Common dental ailments mentioned were dental pain, tooth sensitivity, bleeding gums, tooth decay, mouth odor, gum disease, and tooth fracture. Perceived causes of dental conditions included poor dental hygiene and habits, sugary diets, ignorance, and supernatural forces. Mouth cleaning was mostly done once daily using toothbrush and paste. Other cleaning tools were ground glass, wood ash, charcoal, "epa Ijebu" (a dentrifice), and "orin ata" (a type of chewing stick). Remedies for relieving dental pain included over-the-counter medicines, warm salted water, gin, tobacco (snuff/powdered), cow urine/dung, battery fluid, and various mixtures/ concoctions. Visits to the dentists were mentioned by a few but this was usually as last resort. Main barriers to accessing care from dental care facilities were unaffordability of service charges and fear of extreme treatment measures (extraction). Suggested measures to improve timely access to dental health care included reducing/subsidizing costs of treatments and medications, offering non-extraction treatment options, and oral health education programmes. Conclusion The slum residents experience various forms of dental ailments mostly pain-related. The residents perceived formal dental clinics as unaffordable, thereby engaging in self‐care remedies and harmful oral health practices before seeking professional help. Policymakers and decision-makers may leverage this empirical evidence for the people's education on early dental care and address challenges to affordable, available, and acceptable oral healthcare services among slum residents to improve access to care facilities.